Method for manufacturing magnetocaloric heat exchanger element
By auto-catalyzed chemical deposition on the magnetothermal substrate, a solid metal coating is formed, which solves the problem of insufficient mechanical and chemical stability of existing magnetothermal materials in heat exchangers, and realizes efficient and durable heat exchanger components.
Patent Information
- Application Number
- CN202380039588.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-10
- Filing Date
- 2023-03-09
- Publication Date
- 2025-02-28
AI Technical Summary
Existing magnetothermal materials are difficult to achieve high mechanical and chemical stability in heat exchangers, are prone to corrosion and prone to fracture, especially in water-based heat exchange media.
Auto-catalytic chemical deposition is achieved by providing a magnetothermal substrate with multiple channels or pores and immersing it in a mild aqueous reaction solution to form a robust, durable metal coating to enhance the mechanical and chemical stability of the substrate.
The heat exchanger element with high mechanical and chemical stability under operating conditions is realized, reducing the risk of corrosion and the possibility of fracture, and improving the heat exchange efficiency and the service life of the equipment.
Smart Images

Figure CN119547163A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing a magnetocaloric heat exchanger element. The invention also relates to a heat exchanger element produced by this method, and to a heat pump or a cooling or heating device comprising such a heat exchanger element. The invention also relates to a nickel-based deposition solution and a copper-based deposition solution, in particular for use in said method. Background Art
[0002] In addition to the selection of high-performance functional materials that are suitable for the required temperature range and have appropriate cost-effectiveness, the appropriate design of the magnetocaloric heat exchanger is a prerequisite for the economical use of the theoretically expected energy efficiency gains when using magnetocaloric materials in heat pumps and cooling equipment. This applies to the composition, structure and construction of the magnetocaloric heat exchanger. For example, properties such as low flow resistance, high volume density of magnetocaloric materials, high entropy change during magnetic phase change, manufacturing from cheap raw materials, efficient heat transfer and long service life are all desirable. The latter requires high mechanical and chemical stability under operating conditions (i.e. in the presence of heat exchange medium and forces generated during operation of the equipment). In particular, the flow of the heat exchange medium, the magnetic attraction and the volume changes caused by repeated magnetization (demagnetization) and the associated phase changes.
[0003] The focus on low-critical, inexpensive raw materials makes magnetocaloric materials particularly promising, which mainly consist of readily available transition or main-group metals and the relatively noncritical rare earth metal lanthanum. Noteworthy material classes include Heusler compounds, iron phosphide (Fe2P)-based magnetocaloric compounds, and lanthanum-iron-silicon-based alloys, of which the hydrogenated variants are particularly interesting for cooling applications under ambient conditions due to their increased Curie temperature and high power density. By adjusting the composition, the ideal use range of magnetocaloric compounds (such as lanthanum-iron-silicon-based alloys) can be significantly reduced, so that this class of materials is also suitable for low-temperature applications.
[0004] Magnetocaloric solid materials cannot satisfactorily achieve the desired combination of many of the above-mentioned properties. For example, due to their composition of oxophilic, moderately to strongly alkaline metals (such as lanthanum) and poorly passivating metals (such as iron), they are inherently sensitive to corrosion, and the combined structure of intermetallic materials (such as lanthanum-iron-silicon-manganese alloys and Heusler compounds or iron phosphides) makes them inherently brittle and easy to break. Lanthanum-iron-silicon-manganese alloys that have been hydrogenated to adjust their magnetic properties will lose hydrogen by diffusion even at moderately high temperatures below 100°C, which leads to undesirable changes in their magnetic functions. Near the Curie temperature (which is in the range of room temperature and below for the main target applications), even partial dehydrogenation will lead to a sharp acceleration of the migration of hydrogen remaining in the lattice, which excludes the commercial use of partially hydrogenated lanthanum-iron-silicon alloys due to accelerated aging and performance loss. Therefore, such substrates are incompatible with deposition methods or modification processes that rely on elevated temperatures (such as sintering treatments for reducing coating stress, interdiffusion boundary layers, and improving adhesion or bonding of granular starting materials).
[0005] Due to the high chemical reactivity, non-destructive processing and modification of this material is challenging. Corrosion in the presence of organic or water-based cooling media leads to loss of active material and, depending on the surrounding pH, to accumulation of oxidic, hydrooxidic or soluble oxidation products. Solid corrosion products can enter or adhere to the cooling circuits, leading to losses in heat transfer and deterioration of flow characteristics. In wet chemical coating processes such as electrodeposition, the desired coating reaction competes with the same corrosion process, which in this case can adversely affect coating quality and adhesion. Summary of the invention
[0006] The object of the present invention is to provide a cost-effective, resource-saving, easy to implement, preferably harmless and fault-tolerant process by which durable, strong, chemically and mechanically stable heat exchanger elements with advantageous thermohydraulic and magnetic properties can be manufactured. In particular, low flow resistance of the heat transfer medium flowing through it, high bulk density of the magnetocaloric material, high entropy change during magnetic phase transitions, efficient heat transfer and high material and corrosion stability under application conditions (especially in water-based heat exchanger media) and avoidance of hydrogen embrittlement or losses are desirable. Furthermore, it is necessary to specify a deposition solution suitable for carrying out the process, which is nickel-based on the one hand and copper-based on the other hand.
[0007] This problem is solved according to the invention by a method having the features of claim 1. A corresponding heat exchanger element is the subject matter of claim 19.
[0008] Therefore, the method according to the invention for producing a magnetocaloric heat exchanger element comprises the following steps:
[0009] providing a magnetocaloric substrate having a plurality of channels or holes, preferably forming continuous channels,
[0010] Immersing the substrate in a mild aqueous reaction solution results in the autocatalytic chemical deposition of a metal coating on the substrate surface.
[0011] The substrate is also referred to as a matrix. The reaction solution is also referred to as a deposition solution. The term deposition tank is also used here as a synonym.
[0012] Heat exchanger elements are also called heat transfer elements or regenerator elements. Abbreviations such as heat exchanger, heat transfer or regenerator are also commonly used.
[0013] In this application, the term "magnetocaloric" refers to the property of a substrate that exhibits a technically useful magnetocaloric effect according to the common understanding in the art. This is understood to refer to the phenomenon that when a magnetizable material is exposed to a changing magnetic field, its temperature changes.
[0014] Continuous or continuous channels are to be understood as meaning that they pass through the heat exchanger element from one end thereof to the other, in particular completely through it. Thus, the respective channels have two open ends, wherein one opening is located in a first surface area of the heat exchanger element and the second opening is located in a second surface area different from the first surface area. Thus, a fluid, in particular a liquid, can flow through the respective channels from one opening (inlet) to the other opening (outlet), whereby the flow direction can also be reversed depending on the pressure conditions. Preferably, the channels formed by the holes are arranged overall in such a way that they allow a directional flow through the heat exchanger element in the main flow direction or in the opposite direction.
[0015] In view of the preferred dimensions mentioned below, the pores or channels are also referred to as microchannels.
[0016] "Coating the surface" here means coating the entire inner and outer surface of the substrate which may come into contact with the heat transfer medium during subsequent use as a heat exchanger element. In particular, the walls of the holes or channels should be coated.
[0017] The present invention is based on the consideration that solid magnetocaloric regenerators are not well suited for efficient heat exchange with the surrounding medium due to their limited thermal conductivity. Instead, the present invention seeks ways to create easily accessible large internal surfaces by introducing a suitable pore configuration. While this intensifies the heat exchange, it also increases the challenges in operation and processing: the enlarged surface in contact with the cooling medium exacerbates the corrosion problems, in addition to avoiding undesirable side reactions, the increased geometric complexity of the porous magnetocaloric material places high demands on the consistency and uniformity of the coating technology in question, and due to their size, the fine channels are particularly susceptible to clogging by solid corrosion products.
[0018] As recognized in the context of the present invention, an effective coating technology capable of covering porous patterns of magnetocaloric materials with secondary materials in a non-degrading, controlled and uniform manner, which complements the properties of the substrate and compensates for its weaknesses through the functionality introduced at its surface, is desirable as a technical solution for producing high-performance, price-competitive and robust magnetocaloric heat exchangers. For example, encapsulating the magnetocaloric material in a rigid and plastically deformable coating increases its resistance to fracture and reduces the risk of phase change-induced pulverization, while completely covering the surface with a chemically more stable material improves its corrosion resistance and aging stability. In order not to unnecessarily increase the thermal mass of the system and not to jeopardize the efficient heat transfer from the magnetocaloric material to the surrounding cooling medium, which is a key performance parameter, a thin and poorly insulating coating is ideal.
[0019] In summary, the desired properties (especially high corrosion resistance under operating conditions, mechanical protection of magnetocaloric materials, ductility, high thermal conductivity) can be achieved mainly by metal coatings. Applying these methods to complex-shaped, chemically and physically sensitive magnetocaloric substrates with large internal surfaces, with consistent, defect-free surfaces and good adhesion, is challenging but can be achieved by tailored autocatalytic chemical metal deposition processes that take into account the specific reactivity of the magnetocaloric materials, their geometry and the desired combination of target properties, as described in more detail below.
[0020] The substrates treated according to the invention are particularly suitable for magnetocaloric applications, in particular in cooling devices with water-based heat exchange media. Such heat exchange media are ecologically favorable, have good physical and chemical property data (very high heat capacity, high thermal conductivity, relatively low viscosity), and are available in large quantities at low cost. However, compared to aprotic organic solvents or similar non-aqueous cooling media, they are corrosive, which explains the need to protect the magnetocaloric functional materials from chemical attack according to the invention.
[0021] Advantageous embodiments of the invention, some of which have independent innovative features, are subject matter of the dependent claims in conjunction with the following description.
[0022] Advantageously, the substrate is unitary (in the sense of being monolithic, complete, continuous) and preferably uniformly permeated with continuous pores. Preferably, the pores are substantially rectilinear and arranged parallel to each other, thereby forming a plurality, in particular a plurality, of channels connected in parallel in the direction of flow. However, curved channels that deflect the direction of flow in order to intensify heat exchange at the expense of friction are also included in the invention.
[0023] Preferably, if the diameter of the pores is between 200 and 1000 μm, the pores are preferably monodisperse and preferably have a constant diameter along their course and / or wherein walls are formed between the pores whose wall thickness is less than 1000 μm, preferably less than 600 μm. For pores with a non-circular cross section, the term "diameter" is understood in a general sense as the extension in the direction of the cross section. However, the diameter of the channel can also vary in the longitudinal direction. In particular, there may be steps or offsets.
[0024] Advantageously, the volume proportion of the pores of the substrate is in the range from 10% to 60%, preferably from 20% to 55%, of the total volume.
[0025] In a variation of this concept, before immersion in the reaction solution, the substrate is present in the form of a loose or compacted pile, such as granules, powders, grains or other particles, which are bound together (material bonding or "gluing") by the formed metal coating during the coating process, so that the previously loose pore structure solidifies and becomes permanent. In particular, this means that during the deposition or coating process, the pile material only becomes an overall porous structure or form or object. The individual particles of the pile material are actually building blocks or precursors / precursor particles of the subsequent solid. In general, the substrate can be cast / stacked / assembled / etc. from smaller, initially loose or unbound building units or building blocks (such as particles, spheres, tubes or structured layers), which are then bound together by metallization. These variations are possible for both nickel electroplating and copper electroplating described below.
[0026] Preferably, the substrate is composed of a metal or metal alloy based on a transition group or main group metal or a material based on the rare earth metal lanthanum. The substrate is particularly preferably a Heusler alloy, a magnetocaloric compound of the iron phosphide type or a lanthanum-iron-silicon based alloy, in particular a lanthanum hydride-iron-silicon-manganese alloy.
[0027] Advantageously, the temperature of the deposition bath is in the range of 20° C. to 90° C., preferably below 60° C. The metal coating is preferably performed in such a way that the protective effect and stability of the deposited layer do not depend on treatment at high temperatures, in particular treatment above 90° C. (e.g. sintering treatment). In other words, preferably during the metal coating, during any pretreatment before the coating and / or during any posttreatment after the substrate coating, the temperature effects on the substrate do not exceed 90° C. Preferably, even 60° C. is not exceeded.
[0028] Preferably, during the deposition process, if the entire surface of the substrate, in particular the inner surface of the hole wall, is in continuous contact with the fresh reaction solution, this is achieved by passive flow through the hole caused by micro-convection and / or by the active flow of the reaction solution caused by a pump, etc., whereby, preferably, the substrate is aligned at least temporarily, preferably most of the time, during the deposition process in such a way that the hydrogen bubbles formed during the deposition are automatically removed from the hole. This is particularly achieved by the preferred vertical or inclined orientation of the hole, or preferably by the constant rotation of the substrate in the solution. On the outside of the substrate, a contact surface is formed (for example, by contact or attachment), the scope and durability of which are preferably minimized by selecting the smallest possible number and size and / or by regular rotation or movement. In other words, constant contact points, accumulation of bubbles and stagnation of the reaction solution in the substrate are avoided. By continuous contact with fresh, unused reaction solution, a uniform coating is ensured anywhere on the substrate surface. A preferred version of this embodiment is a planar connected mesh basket in which individual microchannels are placed, and their positions are changed by regular (not necessarily continuous) shaking.
[0029] In the preferred special case of the rotation method, during the deposition process, the substrate is stored and rotated in a receiving cylinder which rotates in the deposition tank. The receiving cylinder preferably has side surfaces which are provided with through-flow openings for the reaction or deposition solution.
[0030] In a first advantageous variant, the deposition bath is a nickel-phosphorus deposition bath, which preferably comprises the following components:
[0031] A nickel (II) source, preferably nickel sulphate;
[0032] a ligand, preferably citrate and / or other carboxylic, hydroxycarboxylic or aminopolycarboxylic acids, preferably in a molar ratio of about 6:1 to 10:1 based on nickel(II), the molar ratio being measured according to the number of nickel(II) binding sites provided by the ligand;
[0033] an alkali, preferably ammonia and / or ammonium salts, such as ammonium sulphate, particularly preferably ammonia to which an ammonium salt is added;
[0034] a catalytic conversion reducing agent, preferably a hypophosphite, such as potassium, sodium and / or ammonium hypophosphite, and / or a hydrazine, a borohydride and / or an aminoborane, preferably in a molar ratio of about 2:1 to 3:1 based on nickel(II);
[0035] Optional stabilizer, preferably lead (Pb) (II) salt, such as lead acetate
[0036] - Optional surface-active compounds, preferably anionic surfactants, such as sodium and / or potassium soaps, organosulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates.
[0037] In a second advantageous variant, the deposition bath is a copper deposition bath, which preferably comprises the following components:
[0038] A source of copper (II), preferably copper sulphate;
[0039] ligands, preferably tartrates and / or other carboxylic acids, hydroxycarboxylic acids or aminopolycarboxylic acids, preferably in a molar ratio of about 5:1 to 10:1 based on copper(II), the molar ratio being measured according to the number of copper(II) binding sites provided by the ligands;
[0040] a base, preferably alkali metal hydroxides and alkali metal carbonates or mixtures thereof, such as sodium hydroxide, potassium hydroxide or sodium carbonate;
[0041] A catalytic conversion reducing agent, preferably formaldehyde and / or glyoxylic acid and other aldehydes, preferably in a molar ratio of about 2:1 to 3:1 based on the number of molar equivalents required to completely reduce copper(II);
[0042] Optional surface active agents, preferably anionic surfactants, such as sodium or potassium soaps, organic sulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates;
[0043] Optional additives, preferably cyanides, such as sodium cyanide and / or nitrogen-based heterocycles, such as polypyridines and / or azoles;
[0044] Optional stabilizers, preferably oxo-anions, sulfur compounds and / or heterocycles;
[0045] - Optional nickel (II) salt, preferably nickel sulfate, preferably in a molar ratio of about 1:4 to 1:8 based on copper (II).
[0046] In order to support the deposition reaction, the deposition solution is advantageously enriched with oxygen during the deposition process, in particular by flushing with introduced bubbles (compressed air) or other oxygen-containing gases or gas mixtures or corresponding bubbles. This is also conducive to starting or supporting the circulation of the solution in the separation container.
[0047] A particular advantage of the process according to the invention is that the metal deposition on the substrate occurs spontaneously, in particular without the prior introduction of catalytically active components such as palladium particles, with uniform coverage in the submicrometer range and in less than 10 minutes, preferably in less than 2 minutes and particularly preferably even in less than 30 seconds.
[0048] In order to promote the start of the deposition reaction, it can be provided that the deposition process is selectively supported by applying a voltage to the substrate or by electrical contact of the substrate with the metal, in particular copper. Advantageously, such support measures are omitted, which reduces the complexity of the equipment and simplifies the process control, but in any case the process according to the invention is compatible or compatible therewith, if necessary or advantageous in special cases.
[0049] Advantageously, the deposition time is selected such that the layer thickness of the metal coating is in the range from 3 to 50 μm, preferably from 10 to 30 μm.
[0050] Advantageously, before the deposition process, the substrate is cleaned in / with an organic solvent, in particular N-methylpyrrolidone, isopropanol, ethanol or acetone, and then, if necessary, dried. Preferably, no further pretreatment of the starting workpiece is required.
[0051] Advantageously, after the deposition process, the coated substrate is simply washed with water and then, if necessary, dried in air. Preferably, no further post-treatment of the coated workpiece is required. Instead, it can be used directly as a heat exchanger component or the like; in particular no thermal post-treatment is required.
[0052] Advantageously, the deposition is electroless, i.e. not electroplating, i.e. no (external) plating voltage is applied. This means that no electrodes are required, which simplifies the metallization. Furthermore, due to the autonomy of the chemical reaction, the profile accuracy of the deposition is particularly high, which occurs simultaneously at all accessible catalytic interfaces, which is necessary for the uniform coating of large inner surfaces of the filament-structured magnetocaloric heat exchanger.
[0053] In addition, the direct wet-chemical growth of the metal film at relatively low temperatures avoids thermal stresses that lead to material degradation (such as dehydrogenation), which is common in gas phase reactions (such as CVD). It is also avoided that hidden, only indirectly accessible internal surfaces and holes with high aspect ratios cannot be coated due to shielding effects and complex vacuum processes on the instrument (such as sputtering) are avoided. It is also possible to omit bonding or coating with relatively low melting point alloys such as solder. This process exposes the workpiece to higher thermal loads and it is difficult to achieve the desired thin and very uniform metal film form (a few microns to tens of microns thick) here, because the molten metal is not very suitable for producing a uniform wetting film due to its high viscosity and surface tension, especially at low thickness. The structural complexity and small size of the components outlined here further aggravate this problem.
[0054] In a possible further development of the process, after the deposition process, and possibly after washing and drying, the coated substrate is immersed in a second temperature-controlled deposition tank with a second autocatalytic chemical reaction solution in order to form a second metal coating on the surface of the previously obtained metal coating.
[0055] Preferably, the magnetocaloric heat exchanger component produced according to the method of the invention is used in a heat pump or a magnetocaloric cooling or heating device, wherein an aqueous or water-based heat exchanger medium preferably flows through the device during operation.
[0056] In addition to or instead of magnetocaloric heat exchanger assemblies, the method according to the invention can also be used to provide other objects made of corrosion-sensitive magnetocaloric materials with a mechanically stable and / or chemically aggressive protective metal coating. Such coatings are particularly suitable for all objects that come into contact with aqueous solutions during operation, or for all objects that are protected from oxidation when in contact with air. In this regard, the invention generally also includes a method for coating corrosion-sensitive objects made of magnetocaloric materials, which objects can be of any shape due to the contour fidelity of the coating, wherein the object forms a substrate immersed in an aqueous reaction solution, and wherein the reaction solution causes the autocatalytic chemical deposition of the metal coating on the surface of the substrate. The process is particularly suitable for objects or substrates permeated with continuous pores or microchannels or with a fine, porous, granular or powdery structure, whereby internal, curved or partially hidden surfaces are also coated as completely and evenly as possible. However, in principle, the walls of large channels can also be coated.
[0057] Another aspect of the present invention, which is considered to have an independent inventive concept, is to provide an aqueous reaction solution for producing a metal coating on a metal substrate by autocatalytic chemical vapor deposition, in particular for use in a process for producing a magnetocaloric heat exchanger element of the above type, comprising the following components:
[0058] A nickel(II) source, preferably nickel sulfate;
[0059] ligand, preferably citrate and / or other carboxylic acids, hydroxycarboxylic acids or aminopolycarboxylic acids, preferably in a molar ratio of about 6:1 to 10:1 based on nickel(II), the molar ratio being measured according to the number of nickel(II) binding sites provided by the ligand;
[0060] a base, preferably ammonia and / or an ammonium salt, such as ammonium sulfate, particularly preferably ammonia to which an ammonium salt is added;
[0061] a catalytic conversion reducing agent, preferably a hypophosphite, such as potassium hypophosphite, sodium hypophosphite and / or ammonium hypophosphite, and / or a hydrazine, a borohydride and / or an aminoborane, preferably in a molar ratio of about 2:1 to 3:1 based on nickel(II);
[0062] an optional stabilizer, preferably a lead(II) salt such as lead acetate;
[0063] Optional surface-active compounds, preferably anionic surfactants, such as sodium and / or potassium soaps, organic sulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates;
[0064] In addition to the above nickel-based coating solution, the present invention also teaches a corresponding copper-based reaction solution, which comprises the following components:
[0065] A source of copper (II), preferably copper sulfate;
[0066] ligand, preferably tartrate and / or other carboxylic acids, hydroxycarboxylic acids or aminopolycarboxylic acids, preferably in a molar ratio of about 5:1 to 10:1 based on copper(II), the molar ratio being measured according to the number of copper(II) binding sites provided by the ligand;
[0067] a base, preferably an alkali metal hydroxide and an alkali metal carbonate or a mixture thereof, such as sodium hydroxide, potassium hydroxide or sodium carbonate;
[0068] catalytic conversion of reducing agents, preferably formaldehyde and / or glyoxylic acid and other aldehydes, preferably in a molar ratio of about 2:1 to 3:1 based on the number of molar equivalents required for complete reduction of copper(II);
[0069] Optional surface-active compounds, preferably anionic surfactants, such as sodium or potassium soaps, organic sulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates;
[0070] Optional additives, preferably cyanides, such as sodium cyanide and / or nitrogen-based heterocyclic compounds, such as polypyridine and / or azole compounds;
[0071] Optional stabilizers, preferably oxyanions, sulfur compounds and / or heterocyclic compounds;
[0072] - Optional nickel (II) salt, preferably nickel sulfate, preferably in a molar ratio of about 1:4 to 1:8 based on copper (II).
[0073] In summary, the present invention describes an autocatalytic chemical deposition process, in particular nickel-phosphorus and copper coatings, which are suitable for magnetocaloric materials, in particular heat-sensitive and chemically sensitive compounds, such as lanthanum hydride-iron-silicon-manganese alloys. Such a process enables gentle (in particular, avoiding undesirable corrosive side reactions and avoiding thermal stresses), uniform and effective coating of metal films, which, due to the excellent deposition consistency, can also be applied to complex substrate geometries, such as the above-mentioned technically particularly relevant porous monolithic configurations. This is ensured by process control and the composition of the deposition solution tailored to the specific substrate reactivity.
[0074] The advantages achieved by the present invention are as follows:
[0075] (i) Demonstration of a reliable autocatalytic chemical coating reaction for corrosion protection of magnetocaloric, temperature-sensitive materials, in particular the first demonstration of a copper plating reaction. Using linear sweep voltammetry, a corrosion potential shift of more than 600 mV was demonstrated for a substrate material consisting of a lanthanum hydride-iron-manganese-silicon alloy; at this value, the corrosion potential is in the range corresponding to pure coated metallic copper ( Figure 5 ), indicating that the shielding of the substrate material from the surrounding electrolyte is reliable. Accompanying scanning electron microscopy examination confirmed the excellent defect-freeness, profile fidelity and uniformity of the copper coating ( Figure 6 , Figure 7 ) and the high quality of the interface between the magnetocaloric lanthanum-iron-manganese-silicon substrate and the copper coating, which showed no obvious signs of oxidation but a close bond between the substrate and the coating ( Figure 7 ).
[0076] (ii) Because the metallization reaction can be initiated spontaneously and reliably simply by immersion in the deposition solution, aggressive pretreatment steps (e.g., etching, pickling, sensitizing or activating the substrate surface) or chemical attack points that attack the substrate and create weak points where corrosion may start prematurely (e.g., oxide deposits that reduce metal film adhesion or are not fully covered and cause holes in the coating) or chemical attack points that show increased susceptibility to corrosion can be avoided. For example, oxide deposits that impair metal film adhesion, or oxide deposits that are not fully covered and cause holes in the coating, or areas of chemical attack that are more susceptible to corrosion or have already been corroded should be completely avoided.
[0077] (iii) The aqueous deposition solution has only a weakly corrosive effect on the magnetocaloric substrate, and the rapid onset of metal deposition quickly leads to a blanket film, minimizing the time that the substrate surface is in direct contact with the solution and could corrode in undesirable side reactions.
[0078] (iv) Direct metallization without pre-treatment steps simplifies process management: savings in production time, costs, materials and waste; higher process reliability because there are fewer interlocking work steps that rely on each other to ensure production quality.
[0079] (v) By omitting aggressive pre-treatment steps, the combined effects of the bath composition inhibiting corrosion and rapid coverage of sensitive surfaces of magnetocaloric materials result in higher quality coatings and avoidance of material damage and weak spots.
[0080] (vi) Uncontrolled bonding reactions between metal ions (especially nickel (II), copper (II)) in the deposition bath and the substrate are avoided, which reactions lead to poor coating adhesion, corrosion and / or the formation of powdery or large amounts of reaction products (reduced nickel or copper, oxidized substrate components).
[0081] (vii) The deposition bath is highly reactive even at an ideal deposition temperature of less than 60 °C, which is significantly lower than the industrially used temperatures for autocatalytic chemical Ni-P and Cu deposition reactions but essential for the integrity of sensitive magnetocaloric substrates, as evidenced by the rapid and spontaneous onset of the deposition reaction and the typical 4–10 μm h-100 Å on these substrate materials. -1The metal deposition on the substrate starts spontaneously in less than 10 minutes, preferably in less than 2 minutes (in particular without the use of catalytically active cores composed of palladium, for example). However, the deposition time selected to obtain the desired layer thickness is usually significantly longer than the start time and usually requires several hours, for example 2 to 4 hours.
[0082] (viii) The method according to the invention enables surface-real and uniform (contour-real) metal deposition on magnetocaloric substrates using simple wet-chemical methods. Complex instrumentation, high energy requirements, high control requirements and the need for a controlled reaction atmosphere (as in the case of gas phase reactions) are avoided. The heat load on the substrate is kept low.
[0083] The configuration proposed here ensures better flow properties and a more favorable surface area-to-volume ratio for the heat exchanger compared to alternative designs such as compacted and sintered particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0084] Embodiments of the present invention are explained in more detail below with reference to the accompanying drawings. They show:
[0085] Figure 1 is a highly simplified exemplary view of a porous monolithic magnetocaloric substrate, here with a large number of continuous, straight, parallel and monodisperse pores,
[0086] Figure 2 The process sequence for coating such substrates is outlined in the form of a flow chart.
[0087] Figure 3 is a schematic representation of an apparatus for coating a substrate, in this case a microchannel substrate stored upright in a reaction solution, and
[0088] Figure 4 is a schematic representation of a rotating pick-up cylinder holding multiple substrates during the coating process as an example of optional substrate metallization with automated sample movement,
[0089] Figure 5 is an electrochemical characterization of the corrosion behavior of an untreated, lanthanum hydride-iron-manganese-silicon alloy substrate, such a substrate copper-plated according to the invention and a pure copper reference sample,
[0090] Figure 6 are scanning electron micrographs at two different magnifications showing a top view of a thin sheet of lanthanum hydride-iron-manganese-silicon alloy coated with copper according to the invention; no exposed alloy substrate is visible, only a well-defined and tightly packed copper film covering the entire surface, and
[0091] Figure 7is a scanning electron micrograph of a fracture edge of a plate coated with copper according to the invention, consisting of a lanthanum hydride-iron-manganese-silicon alloy; the plate (upper part of the picture) can be easily distinguished from the finely crystallized copper film, which is compact, homogeneous and tightly bound together due to its granular structure; moreover, no traces of corrosion are visible at the interface, which confirms the integrity of the coating process. DETAILED DESCRIPTION
[0092] The present invention comprises an integral porous magnetocaloric structure realized by an autocatalytic chemical deposition process, which is mechanically reinforced and protected against corrosion by an external metal coating for use as a long-term stable and efficient temperature conversion component in magnetocaloric heat pumps and cooling devices.
[0093] To this end, a preferred monolithic magnetocaloric substrate is provided which consists of, for example, a lanthanum hydride-iron-silicon-manganese alloy, a Heusler compound or an iron phosphide-based magnetocaloric material and has continuous, ideally parallel and monodisperse pores. Figure 1 An example structure is schematically shown. In this example, the starting product or precursor of the desired heat exchanger assembly formed from an untreated substrate is in the shape of a cuboid with a first end face facing the observer and, correspondingly, a second end face facing away from the observer (not visible). Holes extend through the cube from the first end face to the second end face, thereby forming continuous parallel (micro) channels with walls of substrate material in between, thereby enabling a fluid heat transfer medium (also called refrigerant) to flow directional through the cube in the direction of the arrow or against the direction of the arrow.
[0094] After an optional cleaning step with one or more organic solvents (for example with N-methylpyrrolidone, isopropanol, ethanol or acetone) (but apart from that preferably without further pretreatment steps), the substrate is autocatalytically chemically coated with the metal by immersion in a suitably reactive deposition bath. A detailed description of particularly preferred features of this application can be found below. The desired average coating thickness is generally between 3 μm and 50 μm, ideally between 10 μm and 30 μm. In addition to a single coating, the coating with one or two metals can also be carried out in two separate deposition steps. A flow chart of the overall process is summarized in Figure 2 middle.
[0095] Advantageous configurations use magnetocaloric materials with a maximum (wall) thickness of about 1000 μm, ideally below 600 μm, to ensure good heat transfer of the magnetocaloric functional material, with sufficiently high porosity and uniformly distributed, continuous, linear and monodisperse pores with a diameter of about 200 μm-1000 μm, easy to flow, but at the same time with a sufficiently high volume fraction of magnetocaloric material to provide good power density. To this end, the global porosity should reach 10% to 60%, ideally 20% to 55%. The pores do not have to have a circular cross section; other cross sections are also possible. In particular, elongated or slit-shaped pores are allowed if they are limited to the above values of about 200 μm-1000 μm in one dimension. From the perspective of the cross section, an area of 1 cm2 in the flow direction preferably has tens to hundreds, in particular 100 to 800 microchannels, whereby the surface density of the pores is mainly determined by the size of the pores and their distribution in the magnetocaloric matrix.
[0096] Suitable integral porous substrates for coating can be achieved, for example, constructively by stacking and joining (structured) plates or by 3D printing, on the contrary, for example, by water jet cutting or wire erosion of solid materials. These details should be understood as examples. The process described herein assumes that a suitable substrate is provided, preferably with a high-quality surface that is chemically reduced or at least not significantly oxidized. Feasibility has been empirically proven, and corresponding samples are commercially available. However, the details of the initial substrate production are not the subject of this specification.
[0097] As deposition baths, those for the production of nickel-phosphorus and copper coatings are of particular note. While nickel-phosphorus stands out primarily due to its high corrosion resistance, copper is particularly recommended for this application area due to its plasticity and excellent thermal conductivity.
[0098] The nickel-phosphorus deposition bath preferably comprises:
[0099] (i) a nickel (II) source (preferably nickel sulfate), which provides the precursor ions required for the metal coating (preferably in the range of 0.03-0.4 mol L-1, especially 0.06-0.3 mol L-1);
[0100] (ii) ligands (preferably citrates or other carbonic acids, hydroxycarboxylic acids or aminopolycarboxylic acids) (preferably in the range of 0.04-0.55 mol·L-1, in particular 0.09-0.4 mol·L-1), which serve to ensure the solubility of the metal salt used in the alkaline medium, as well as to complex ions and adjust their reactivity;
[0101] (iii) a base and an ammonium salt, the base is preferably ammonia (preferably in the range of 0.6-2.4 mol·L-1, in particular 1.0-2.0 mol·L-1), which is used to set a sufficiently high pH value to reduce the corrosiveness of the solution to the substrate; the ammonium salt, such as ammonium sulfate (preferably in the range of 0.3-1.2 mol L-1, in particular 0.5-1.0 mol L-1), is particularly preferably supplemented with ammonium salt to form a buffer, and then ammonia is continuously or batchwise dosed after half of the reaction time to keep the pH stable;
[0102] (iv) a sufficiently strong reducing agent (preferably a hypophosphite, such as potassium hypophosphite, sodium hypophosphite or ammonium hypophosphite, and also a hydrazine, a borohydride or an aminoborane) for catalytic conversion (preferably in the range of 0.1-0.5 mol L-1, in particular 0.2-0.35 mol L-1);
[0103] (v) optional but highly recommended stabilizers to prevent homogeneous nucleation (e.g. lead (II) salts such as lead acetate) (e.g. in the range of 2-25 ppm, especially 4-9 ppm);
[0104] (vi) optional but highly recommended surfactant compounds to improve wettability of the substrate surface, accelerate separation of gas bubbles on the substrate to counteract deposition heterogeneity, and optimize solution reactivity, but avoid formation of excessively stiff foam or precipitation of poorly soluble metal soaps, which would block substrate pores and counteract uniform metallization (preferably anionic surfactants such as sodium or potassium soaps, organic sulfonates, and sulfates, but also neutral surfactants such as polysorbates) (e.g., up to 2 mmol L -1 , especially 0.01-0.7mmol L -1 ).
[0105] The copper deposition bath preferably comprises:
[0106] (i) a copper (II) source (preferably copper sulfate), which provides the precursor ions required for the metal coating (preferably in the range of 0.02-0.2 mol L -1 range, especially 0.03-0.09 mol L -1 );
[0107] (ii) ligand (preferably tartrate or other carbonic acid, hydroxycarboxylic acid or aminopolycarboxylic acid) (preferably 0.06-0.6 mol·L -1 In the range of 0.1-0.3 mol·L -1 ), which serve to ensure the solubility of the metal salts used in alkaline media, as well as to complex ions and adjust their reactivity;
[0108] (iii) a base (preferably an alkali metal hydroxide and an alkali metal carbonate or a mixture thereof, such as sodium hydroxide, potassium hydroxide or sodium carbonate) (preferably in the range of 0.15-0.6 mol L -1 range, especially 0.2-0.4 mol L -1 ), which is used to adjust the pH value to a sufficiently high level;
[0109] (iv) a sufficiently strong catalytic conversion reducing agent (preferably formaldehyde, but also including glyoxylic acid and other aldehydes) (preferably in the range of 0.15-1.0 mol L -1 range, especially 0.2-0.5 mol L -1 );
[0110] (v) optional but highly recommended surfactant compounds to improve wettability of the substrate surface, accelerate separation of gas bubbles on the substrate to counteract deposition heterogeneity, and optimize solution reactivity, but avoid formation of excessively hard foam or precipitation of poorly soluble metal soaps, which would block substrate pores and counteract uniform metallization (preferably anionic surfactants such as sodium or potassium soaps, organic sulfonates and sulfates, but also neutral surfactants such as polysorbates) (e.g. up to 2 mmol L -1 , especially 0.01-0.7mmol L -1 );
[0111] (vi) optional but highly recommended additives to improve ductility and stabilize the deposition solution (preferably cyanides such as sodium cyanide or nitrogen-based heterocycles such as polypyridine or azole) (exemplary up to 3 mmol L -1 , especially 0.02-0.8mmol L -1 );
[0112] (vii) optional but highly recommended additional stabilizers to prevent homogeneous nucleation under deposition conditions (e.g., oxygen-containing anions, sulfur-containing compounds, heterocycles) (e.g., up to 1 mmol L -1 );
[0113] (viii) optional but highly recommended nickel (II) salt (preferably nickel sulfate) for optimizing reactivity (e.g. at 0.003-0.03 mmol L -1 In the range of 0.006-0.018mmol L -1 ).
[0114] To start the reaction, the substrate is simply immersed in a deposition bath heated to a reaction temperature of less than 90° C. (ideally less than 60° C.). Deposition begins spontaneously and uniformly over the entire substrate surface in less than 10 minutes (ideally less than 2 minutes), indicated by the generation of reactive gases, but can be additionally stimulated by applying a voltage, electrical contact of the substrate with a less noble metal (such as aluminum), or by contact with metallic copper. The bath is preferably flushed with bubbles during heating and deposition to enrich it with oxygen and circulate it. Other oxygen-containing gases or pure oxygen may also be injected.
[0115] When the substrate is fixedly placed in the deposition solution, it is preferred to ensure that the holes are arranged diagonally vertically so that the hydrogen bubbles formed during the deposition process are automatically and quickly removed from the holes by buoyancy, which ensures permanent wetting of the entire substrate surface by the deposition solution (thereby obtaining a uniform coating) and continuous renewal of the deposition solution inside the substrate. This can be achieved, for example, by leaning the substrates sideways against the container wall, placing them on one side of a raised area of the container bottom, using a concavely curved container bottom, or placing the substrates on a grid or similar support suspended in the solution.
[0116] After a deposition time corresponding to the desired layer thickness, the substrate is removed from the solution, preferably rinsed thoroughly with water, dried in air and is ready for integration into a heat pump or cooling device. Advantageously, no further post-treatment steps are required.
[0117] An example of the above reaction process is Figure 3 shown. In order to avoid permanently inaccessible contact points between the substrate to be metallized and the holder, which could lead to weak spots or holes in the coating, it is also recommended to regularly turn the sample. Ideally, this should be done automatically, while maintaining as open access to the deposition bath as possible and preventing the substrate from falling out of the sample holder. It is also important to avoid rubbing of several substrates against each other and damage to brittle substrate materials or coatings due to friction or impact with the moving sample holder (e.g. due to excessively hard surfaces).
[0118] In summary, Figure 3The deposition pool 2 used in the method of the present invention is shown. A deposition solution 6 or liquid of the above type is located in a suitable container 4, which is preferably accessible from above and is preferably trough-shaped. The container 4 contains one or more supports 8 for the substrate 10 to be coated, which, as mentioned above, is preferably a single body of magnetocaloric material penetrated by parallel holes or (micro) channels 12. The substrate 10 is preferably arranged in a manner in which the microchannels 12 are arranged vertically. In this example, the support 8 is mounted on the bottom of the container 4 and supports the inserted or loosely placed substrate 10 from below. The appropriate shape minimizes the contact between the support 8 and the substrate 10 to a few point contacts. The filling level of the deposition solution 6 is such that the substrate 10 is completely immersed in the deposition solution 6. Due to the selected mounting method, the substrate 10 is in contact with the deposition solution 6 on all sides. In particular, the lower side and upper side of the substrate 10 with the inlet and outlet openings of the microchannel 12 are easily accessible. The deposition solution 6 is adjusted to the desired processing temperature by a temperature control device not shown here.
[0119] Through an air hose 14 immersed in the deposition solution 6, an air flow is introduced into the deposition solution 6 at its outlet with the aid of an associated compression pump or the like. The gas bubbles 16 released in this way and eventually rising enrich the deposition solution 6 with oxygen and circulate it in the container 4, thus functioning to a certain extent as an agitator. In this way, during the deposition process, the deposition solution 6 flows directionally from bottom to top through the pores or microchannels 12 of the substrate 10 (and along the outer walls), as indicated by the flow arrows 42. As a result, the entire inner and outer surfaces of the substrate 10, including the pore walls, are covered with a uniform thin metal coating 40. The hydrogen bubbles 18 released during the autocatalytic coating reaction rise in the microchannels 12 and escape to the surrounding atmosphere at the surface of the deposition solution 6.
[0120] Certainly, also can be coated several substrates adjacent to each other simultaneously in the suitable large groove with a plurality of supports.In this case, preferably guarantee to have enough large distance between the workpiece (substrate) to be coated, these workpieces should not contact each other in the processing.
[0121] A possible improved configuration is to store the substrate to be coated separately in a separate chamber provided with an opening and rotating in a cylinder in a deposition tank, the deposition tank being composed of a material that is not chemically attacked by the deposition tank and is soft enough at least in the area in contact with the substrate (the inner wall of the chamber) to prevent mechanical damage to the substrate during the coating process (e.g., silicon-coated metal).
[0122] Figure 4Such a receiving cylinder 20 is schematically shown. The receiving cylinder 20 is designed as a hollow cylinder with a side surface 22 and an end cap or end wall 24 that closes the interior. From a longitudinal perspective, the interior of the cylinder is subdivided into individual chambers 28 or compartments by an intermediate wall 26, each of which is used to accommodate a single workpiece (substrate 10). In order to insert and subsequently remove the corresponding monomer or workpiece, each chamber is provided with an inlet 30 of sufficient size, which can be closed during the deposition process by a lockable closure cover 32. This prevents the workpiece from falling off during the coating process. In order to ensure that there is enough flow through each chamber 28 during the coating process, the side surface 22 of the receiving cylinder 20 has a large number of flow openings 34, such as slit-shaped openings, which are distributed around the circumference and in the longitudinal direction, and the opening is kept very small so that the workpiece cannot pass. At the end face, the receiving cylinder 20 is connected to a drive shaft 36, which is rotatably mounted in the deposition tank 2 and is preferably driven by a motor so that the receiving cylinder 20 can rotate in the deposition tank 2 during the deposition or coating process. The axis of rotation is preferably aligned horizontally, so that the individual workpieces tumble in the lower region of the receiving cylinder 20 at a moderately high rotational speed and are constantly turned over.
[0123] Direct autocatalytic wet-chemical coating of magnetocaloric substrates has in fact demonstrated effective corrosion protection in tests, for example by reducing the corrosion potential to the values of the coated metal measured in linear voltammetric measurements, which shows that the coating avoids defects extremely well.
[0124] For example, refer to Figure 5 , which shows a graphical representation of the corrosion potential measured on various samples, namely an untreated lanthanum hydride-iron-manganese-silicon alloy substrate, a substrate plated with copper according to the present invention, and a pure copper reference sample. The measurements are based on a three-electrode setup with a platinized titanium (Ti) grid as counter electrode, various metal plates as working electrodes, and a mercury-mercury sulfate (Hg-Hg2SO4) reference electrode. Further parameters are: electrolyte: high purity (>18.2 MΩcm) water mixed with 100 mM TRIS buffer and 20 mM citric acid; feed rate: 0.25 mV / s; controlled using a Gamry Reference 600 potentiostat.
[0125] Even complex-shaped magnetocaloric workpieces, such as the aforementioned microchannel monoliths, can be easily, reliably, quickly, and uniformly metallized via the developed deposition reactions using a scalable, material-friendly process based on inexpensive base chemicals.
[0126] The high quality of the deposited metal films was also confirmed by scanning electron microscopy (see Figure 6 and 7 ), which is also demonstrated by the successful, uniform, and opaque metallization of the inner surface of the microchannel monomer.
[0127] All deposition and processing steps are actually carried out at relatively low temperatures. There is no need for more thermally activated methods for deposition (e.g. chemical or physical vapor phase synthesis, immersion in molten metal) or for improving the coating quality (e.g. improving coating adhesion, sintering the coating or reducing stresses by heat treatment), which cannot be easily applied to temperature-sensitive magnetocaloric substrates.
[0128] The mechanical toughness of the copper films was investigated in fracture tests, where it was demonstrated that the metallic coating increased the mechanical stability and fracture resistance of the inherently brittle magnetocaloric monomers.
[0129] The improved quality of the metallized magnetocaloric microchannel substrates in terms of coating uniformity, freedom from defects and corrosion protection by avoiding aggressive process steps is also demonstrated: Compared to the direct metallization presented here, other common pretreatment methods, such as etching the substrate surface with dilute acids (e.g. hydrochloric acid or sulfuric acid) or immersion in sensitizing and activating solutions (e.g. hydrochloric acid solutions of stannous chloride or cuprous chloride), which are common in the preparation of chemical metallization, lead to a decrease in the adhesion of the metal film and to visible and obvious corrosion marks. In this case, the use of a catalyst is not required, as the reaction is initiated spontaneously when the substrate is immersed in the deposition solution.
[0130] Reference Symbols List
[0131] 2 Sedimentation Tank
[0132] 4 Containers
[0133] 6. Reaction or deposition solution
[0134] 8 Bracket
[0135] 10 base
[0136] 12 (micro) channels
[0137] 14 Air hose
[0138] 16 Air Bubbles
[0139] 18 Hydrogen Bubbles
[0140] 20 receiving cylinder
[0141] 22 side surface
[0142] 24 end wall
[0143] 26 Middle wall
[0144] Room 28
[0145] 30 entrance openings
[0146] 32 closed cap
[0147] 34 Flow openings
[0148] 36 Drive shaft
[0149] 40 Metal coating
[0150] 42 Flow direction arrow
[0151] 44 Bottom flow area
Claims
1. A method for manufacturing a magnetocaloric heat exchanger element, comprising the following steps: providing a magnetocaloric substrate (10) having a plurality of flow-through channels (12) or holes, which preferably form continuous channels (12), • Immersing the substrate (10) in a mild aqueous reaction solution (6) results in the autocatalytic chemical deposition of a metal coating (40) on the surface of the substrate (10).
2. The method according to claim 1, wherein: The substrate (10) is unitary and preferably uniformly permeated with continuous pores.
3. The method according to claim 1 or 2, wherein: The pores have a diameter of 200 μm to 1000 μm, the pores are preferably monodisperse and preferably have a constant diameter along their course, and / or wherein walls are formed between the pores, the wall thickness of which is less than 1000 μm, preferably less than 600 μm.
4. A method according to any one of the preceding claims, wherein: The volume fraction of pores of the substrate (10) is in the range of 10% to 60% of the total volume, preferably in the range of 20% to 55%.
5. The method according to claim 1, wherein: Before being immersed in the reaction solution (6), the substrate (10) is present in the form of loose or compacted piles or stacks of smaller structural units, such as particles, spheres, tubes or structured layers, which are bound together by the formed metal coating during the coating process.
6. A method according to any one of the preceding claims, wherein: The substrate (10) is a Heusler alloy, an iron phosphide type magnetocaloric compound or a lanthanum-iron-silicon based alloy, in particular a lanthanum hydride-iron-silicon-manganese alloy.
7. A method according to any one of the preceding claims, wherein: The temperature of the reaction solution (6) ranges from 20 to 90°C, preferably below 60°C.
8. A method according to any one of the preceding claims, wherein: The entire surface of the substrate (10), in particular the inner surface of the pore walls, is always in contact with fresh reaction solution (6) during the deposition process, which is achieved by passive flow through the pores caused by microconvection and / or active flow of the reaction solution (6) through the pores caused by a pump or the like, and wherein, preferably, the substrate (10) is oriented at least temporarily, preferably most of the time, during the deposition process in such a way that hydrogen bubbles formed during the deposition are automatically removed from the pores.
9. A method according to any one of the preceding claims, wherein: The reaction solution (6) is effective as a nickel-phosphorus deposition bath.
10. The method according to claim 9, wherein: The reaction solution (6) comprises the following components: A nickel(II) source, preferably nickel sulfate; ligand, preferably citrate and / or other carboxylic acids, hydroxycarboxylic acids or aminopolycarboxylic acids, preferably in a molar ratio of about 6:1 to 10:1 based on nickel(II), the molar ratio being measured according to the number of nickel(II) binding sites provided by the ligand; a base, preferably ammonia and / or an ammonium salt, such as ammonium sulfate, particularly preferably ammonia to which an ammonium salt is added; a catalytic conversion reducing agent, preferably a hypophosphite, such as potassium hypophosphite, sodium hypophosphite and / or ammonium hypophosphite, and / or a hydrazine, a borohydride and / or an aminoborane, preferably in a molar ratio of about 2:1 to 3:1 based on nickel(II); an optional stabilizer, preferably a lead(II) salt such as lead acetate; - Optional surface-active compounds, preferably anionic surfactants, such as sodium and / or potassium soaps, organic sulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates.
11. The method according to any one of claims 1 to 8, wherein: The reaction solution (6) is effective as a copper deposition bath.
12. The method according to claim 11, wherein: The reaction solution (6) comprises the following components: A source of copper (II), preferably copper sulfate; ligands, preferably tartrates and / or other carboxylic acids, hydroxycarboxylic acids or aminopolycarboxylic acids, preferably in a molar ratio of about 5:1 to 10:1 based on copper(II), the molar ratio being measured according to the number of copper(II) binding sites provided by the ligands; a base, preferably an alkali metal hydroxide and an alkali metal carbonate or a mixture thereof, such as sodium hydroxide, potassium hydroxide or sodium carbonate; a catalytic conversion reducing agent, preferably formaldehyde and / or glyoxylic acid and other aldehydes, preferably in a molar ratio of about 2:1 to 3:1 based on the number of molar equivalents required for complete reduction of copper(II); Optional surface-active compounds, preferably anionic surfactants, such as sodium or potassium soaps, organic sulfonates and / or sulfates, and / or neutral surfactants, such as polysorbates; Optional additives, preferably cyanides, such as sodium cyanide and / or nitrogen-based heterocyclic compounds, such as polypyridine and / or azole compounds; Optional stabilizers, preferably oxyanions, sulfur compounds and / or heterocyclic compounds; - Optional nickel (II) salt, preferably nickel sulfate, preferably in a molar ratio of about 1:4 to 1:8 based on copper (II).
13. A method according to any one of the preceding claims, wherein: The metal deposition on the substrate (10) starts spontaneously, in particular without the prior introduction of catalytically active components such as palladium particles, with uniform coverage in the submicrometer range and in less than 10 minutes, preferably less than 2 minutes, particularly preferably less than 30 seconds.
14. A method according to any one of the preceding claims, wherein: After the deposition process, and optionally after cleaning and drying, the coated substrate (10) is immersed in a second temperature-controlled deposition bath with a second autocatalytic chemical reaction solution to form a second metal coating on the surface of the previously obtained metal coating.
15. A method according to any one of the preceding claims, wherein: Before the substrate (10) is immersed in the reaction solution (6), the substrate surface is not subjected to any pre-treatment steps from the following: etching, pickling, grinding, polishing, sensitization and / or activation.
16. The method according to claim 15, wherein: Before the substrate (10) is immersed in the reaction solution (6) for pretreatment, the substrate (6) is cleaned with water and / or an organic solvent, if necessary, and then dried.
17. A method according to any one of the preceding claims, wherein: The deposition was carried out in the absence of an electric current.
18. A method according to any one of the preceding claims, wherein: After metal coating, a heat transfer fluid, in particular water or an aqueous solution, can flow through the channels (12) or holes.
19. A magnetocaloric heat exchanger element manufactured by a method according to any one of the preceding claims.
20. A heat pump or cooling or heating device comprising a heat exchanger element according to claim 20.